Boundary Stabilization of Memory Type for the Porous-Thermo-Elasticity System - Abdelaziz Soufyane; Mounir Afilal; Mama Chacha (Abstract and Applied Analysis)
We consider the one-dimensional viscoelastic Porous-Thermo-Elastic system. We establish a general decay results. The usual exponential and polynomial decay rates are only special cases.